2020
DOI: 10.3389/fncom.2020.588943
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Synergy Extrapolation for Predicting Unmeasured Muscle Excitations from Measured Muscle Synergies

Abstract: Electromyography (EMG)-driven musculoskeletal modeling relies on high-quality measurements of muscle electrical activity to estimate muscle forces. However, a critical challenge for practical deployment of this approach is missing EMG data from muscles that contribute substantially to joint moments. This situation may arise due to either the inability to measure deep muscles with surface electrodes or the lack of a sufficient number of EMG channels. Muscle synergy analysis (MSA) is a dimensionality reduction a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 69 publications
2
50
0
Order By: Relevance
“…Furthermore, it remains unclear whether the proposed muscle synergy extrapolation method based on non-negative matrix factorisation is sufficiently sensitive to capture spasticity provoked EMG activations commonly used to inform clinical decision making in children with CP 41 . Although recent study 42 found synergy extrapolation method promising, it is yet to explore how neuromusculoskeletal model would perform when synergies extracted from two groups of population (healthy and impaired) are combined and used as input. Future use of the proposed synergy extrapolation method could be combined with neuromusculoskeletal models to predict internal biomechanics in children with CP.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it remains unclear whether the proposed muscle synergy extrapolation method based on non-negative matrix factorisation is sufficiently sensitive to capture spasticity provoked EMG activations commonly used to inform clinical decision making in children with CP 41 . Although recent study 42 found synergy extrapolation method promising, it is yet to explore how neuromusculoskeletal model would perform when synergies extracted from two groups of population (healthy and impaired) are combined and used as input. Future use of the proposed synergy extrapolation method could be combined with neuromusculoskeletal models to predict internal biomechanics in children with CP.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the influence of pre-processing, except for LPFs, has not been studied in this study. Previous studies suggested that different band-pass filters, EMG normalization methods, and output normalization methods slightly influenced muscle weightings ( Banks et al, 2017 ; Shuman et al, 2017 ; Kieliba et al, 2018 ; Ao et al, 2020 ). In particular, Shuman et al (2017) suggested that muscle weightings were more similar in different LPF conditions for EMG data normalized to unit variance than peak amplitude in children.…”
Section: Discussionmentioning
confidence: 99%
“…While calibration of activation dynamics and muscle-tendon model parameter values is built into the EMG-driven modeling process, several practical challenges exist with collecting EMG data from all muscles that contribute significantly to a specified movement task ( Sartori et al, 2014 ; Péter et al, 2019 ; Zonnino and Sergi, 2019 ; Ao et al, 2020 ; Gurchiek et al, 2020 ). First, surface electrodes, which are non-invasive and easily applied, cannot measure EMG signals from deep muscles that contribute significantly to joint moments.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the muscle synergy concept has been investigated for estimating muscle activations via SO or muscle excitations via EMG-driven modeling ( Bianco et al, 2018 ; Ao et al, 2020 ; Michaud et al, 2020 ; Shourijeh and Fregly, 2020 ). A muscle synergy consists of a time-varying synergy excitation (or activation) and a corresponding time-invariant synergy vector containing weights that define how the synergy excitation (or activation) contributes to the excitation (or activation) of all muscles ( Cappellini et al, 2006 ; Tresch et al, 2006 ; Ting and Chvatal, 2010 ; Banks et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%